Effect of Aging Duration on Antidepressant Activity and Sensory Properties of Whey Kefir-Fermented Solo-Bulb Black Garlic (Biosaintifika: Journal of Biology & Biology Education, 2026)
Depression is a prevalent mental disorder worldwide, and conventional antidepressants often cause side effects that reduce patients’ quality of life. Therefore, developing safer natural alternatives is essential. Solo-Bulb Black Garlic (SBBG), a fermented single-clove garlic, exhibits various health benefits, including potential antidepressant activity. This study evaluated the antidepressant effect of whey kefir–fermented SBBG aged for 7, 14, and 21 days in male mice subjected to chronic mild stress (CMS). Antidepressant activity was assessed using the Forced Swimming Test (FST) by measuring immobility, swimming, and climbing behavior, while leukocyte and erythrocyte counts indicated immune responses. The SBBG-21 group exhibited the greatest reduction in immobility duration (1.08 ± 0.30 minutes), accompanied by increased swimming (1.39 ± 0.11 minutes) and climbing (1.53 ± 0.20 minutes) durations. Leukocyte (7.89 × 10³ cells/µL) and erythrocyte (6.19 × 10⁶ cells/µL) counts were close to normal levels. Organoleptic scores for SBBG21 were highest for color (3.54±1.29), aroma (3.17±1.29), taste (3.00 ±1.28), texture (3.35±1.08), and overall preference (3.20±1.11). These results indicate that whey kefir-fermented SBBG aged for 21 days has potential as a functional food with antidepressant properties. It also offers a safer natural alternative to conventional antidepressants, with good acceptability and the potential to improve mental health and quality of life. Furthermore, this research supports SDGs 3 by promoting alternative strategies for managing depression and SDGs 12 by utilizing natural fermentation processes and value-added agricultural products.